2019
DOI: 10.3390/antiox8080294
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress, Irrigation and Concentrations of Pentacyclic Triterpenes and Phenols in Olea europaea L. cv. Picual Olive Trees

Abstract: Pentacyclic triterpenes and phenols are two types of bioactive molecules found in olive trees that have important activities related to health and disease prevention. Triterpenes, including oleanolic acid, maslinic acid, erythrodiol and uvaol, show antitumoral activities, and phenols such as oleuropein, tyrosol, and hydroxytyrosol are natural antioxidants. The concentration of these metabolites is considered a marker of the quality of olives and olive oil. In recent years, a lack of rain water has caused impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
4
14
1
Order By: Relevance
“…its eco-physiological response to irrigation is very high. particularly in critical moments of its vegetative cycle [101][102][103][104][105][106][107]. This allows These findings support our hypothesis that remote sensing data could be used to identify olive cultivars.…”
Section: 1on the Importance Of Olive Variety Discriminationsupporting
confidence: 81%
See 1 more Smart Citation
“…its eco-physiological response to irrigation is very high. particularly in critical moments of its vegetative cycle [101][102][103][104][105][106][107]. This allows These findings support our hypothesis that remote sensing data could be used to identify olive cultivars.…”
Section: 1on the Importance Of Olive Variety Discriminationsupporting
confidence: 81%
“…its eco-physiological response to irrigation is very high. particularly in critical moments of its vegetative cycle [101][102][103][104][105][106][107]. This allows for stabilization of the inter-annual variability in olive production which is a marked characteristic of olive trees.…”
Section: On the Importance Of Olive Variety Discriminationmentioning
confidence: 99%
“…Results of this study demonstrated that the method of extraction used is appropriated for the quantification of the concentration of these compounds in stem samples. The profile described for stem is likely to the found in leaf in which, also this four triterpenic compounds are found [11] although with concentration in leaf higher that in stem. The presence of MA, OA, EO and UO indicate that β-amyrin synthase is present in this organ and it is implied in the biosynthesis pathway of MA, OA and EO and that α-amyrin synthase is also present in this organ and it is implied in biosynthesis of UO.…”
Section: Resultsmentioning
confidence: 77%
“…Concurrently with alterations in temperature, climate change will also trigger variations in current precipitation patterns, modifying not only the precipitation levels but also changing the typical periods where rainfall occurs, causing periods of drought stress and flooding events [63,[127][128][129][130][131]. Moreover, these changes will likely be accompanied by an increase in water demand as the global population grows [81].…”
Section: Drought Stressmentioning
confidence: 99%